Identification of novel sphingolipid-binding motifs in mammalian membrane proteins - Björkholm, Patrik; Ernst, Andreas M.; Wieland, Felix T.; Brügger, Britta (Biochimica et biophysica acta. Biomembranes, 2014)
Specific interactions between transmembrane proteins and sphingolipids is a poorly understood phenomenon, and only a couple of instances have been identified. The best characterized example is the sphingolipid-binding motif VXXTLXXIY found in the transmembrane helix of the vesicular transport protein p24. Here, we have used a simple motif-probability algorithm (MOPRO) to identify proteins that contain putative sphingolipid-binding motifs in a dataset comprising proteomes from mammalian organisms. From these motif-containing candidate proteins, four with different numbers of transmembrane helices were selected for experimental study: i) major histocompatibility complex II Q alpha chain subtype (DQA1), ii) GPI-attachment protein 1 (GAA1), iii) tetraspanin-7 TSN7, and iv), metabotropic glutamate receptor 2 (GRM2). These candidates were subjected to photo-affinity labeling using radiolabeled sphingolipids, confirming all four candidate proteins as sphingolipid-binding proteins. The sphingolipid-binding motifs are enriched in the 7TM family of G-protein coupled receptors, predominantly in transmembrane helix 6. The ability of the motif-containing candidate proteins to bind sphingolipids with high specificity opens new perspectives on their respective regulation and function.